Carotid blowout syndrome in pharyngeal cancer patients treated by hypofractionated stereotactic re-irradiation using CyberKnife: A multi-institutional matched-cohort analysis. Issue 1 (April 2015) - Yamazaki, Hideya; Ogita, Mikio; Himei, Kengo; Nakamura, Satoaki; Kotsuma, Tadayuki; Yoshida, Ken; Yoshioka, Yasuo
Abstract Background and purpose Although reirradiation has attracted attention as a potential therapy for recurrent head and neck tumors with the advent of modern radiotherapy, severe rate toxicity such as carotid blowout syndrome (CBOS) limits its potential. The aim of this study was to identify the risk factors of CBOS after hypofractionated stereotactic radiotherapy (SBRT). Methods and patients We conducted a matched-pair design examination of pharyngeal cancer patients treated by CyberKnife reirradiation in four institutes. Twelve cases with CBOS were observed per 60 cases without CBOS cases. Prognostic factors for CBOS were analyzed and a risk classification model was constructed. Results The median prescribed radiation dose was 30 Gy in 5 fractions with CyberKnife SBRT after 60 Gy/30 fractions of previous radiotherapy. The median duration between reirradiation and CBOS onset was 5 months (range, 0–69 months). CBOS cases showed a median survival time of 5.5 months compared to 22.8 months for non-CBOS cases (1-year survival rate, 36% vs.72%; p = 0.003). Univariate analysis identified an angle of carotid invasion of >180°, the presence of ulceration, planning treatment volume, and irradiation to lymph node areas as statistically significant predisposing factors for CBOS. Only patients with carotid invasion of >180° developed CBOS (12/50, 24%), whereas no patient with tumor involvement less than a half semicircle around the carotid artery developed CBOS (0/22, 0%, p = 0.03). Multivariate Cox hazard model analysis revealed that the presence of ulceration and irradiation to lymph nodes were statistically significant predisposing factors. Thus, we constructed a CBOS risk classification system: CBOS index = (summation of risk factors; carotid invasion >180°, presence of ulceration, lymph node area irradiation). This system sufficiently separated the risk groups. Conclusion The presence of ulceration and lymph node irradiation are risk factors of CBOS. The CBOS index, including carotid invasion of >180°, is useful in classifying the risk factors and determining the indications for reirradiation.